Business Managed Infrastructure Architecture of Information Systems - Kisimov, Valentin (Research Papers, 2009)
Generally, there is mismatching between the speed of business changes and the speed of the supporting ICT changes. The modifications of the business conditions are implemented via the modification of the business models of business processes. It could be very good if those business modifications are followed by synchronous modifications in the supporting ICT system. If this can be done, then the ICT systems would be “agile” systems.The current article presents new infrastructure architecture, capable to follow synchronously the modifications in the business processes. The synchronicity means automatically supporting the new business rules, or with small and quickly made changes to support the new modifications in the business processes. It is offered to use Service Oriented Architecture (SOA), where two infrastructure components are made infrastructure services:Network components;Computing resources components.Network components are made infrastructure services in two directions: Business communications and Dynamic network elements.Also, it is offered an approach for dynamic requesting and using of computing resources, not according the parallel algorithmic needs, but according the correlation between the business processes. In the article is offered the approach of presenting business processes specification via infrastructure services and dynamic requesting computational resources. It is developed a new method for synchronous following of the business modification by the infrastructure components, in which the business processes changes will be followed synchronously by ICT changes.